The role of telehealth in sepsis care in rural emergency departments: A qualitative study of emergency department sepsis telehealth user perspectives. - Nicholas M Mohr; Kimberly A S Merchant; Brian M Fuller; Brett Faine; Luke Mack; Amanda Bell; Katie DeJong; Edith A Parker; Keith Mueller; Elizabeth Chrischilles; Christopher R Carpenter; Michael P Jones; et al. (PLoS ONE)
Purpose Sepsis is a leading cause of hospitalization and death in the United States, and rural patients are at particularly high risk. Telehealth has been proposed as one strategy to narrow rural-urban disparities. The objective of this study was to understand why rural emergency department (ED) staff use provider-to-provider telehealth (tele-ED) and how tele-ED care changes the care for rural patients with sepsis. Methods We conducted a qualitative interview study between February 15, 2022, and May 22, 2023, with participants from upper Midwest rural EDs and tele-ED hub physicians in a single tele-ED network that delivers provider-to-provider consultation for sepsis patients. One interviewer conducted individual telephone interviews, then we used standard qualitative methods based on modified grounded theory to identify themes and domains. Findings We interviewed 27 participants, and from the interviews we identified nine themes within three domains. Participants largely felt tele-ED for sepsis was valuable in their practice. We identified that telehealth was consulted to facilitate interhospital transfer, provide surge capacity for small teams, to adhere with provider scope-of-practice policies, for inexperienced providers, and for patients with increased severity of illness or complex comorbidities. Barriers to tele-ED use and impact included increased sepsis care standardization, provider reluctance, and sepsis diagnostic uncertainty. Additionally, we identified that real-time education and training were important secondary benefits identified from tele-ED use. Conclusions Tele-ED care was used by rural providers for sepsis treatment, but many barriers existed that may have limited potential benefits to its use.